الفرصة حدودها ومنزلتها في القرآن الكريم - الحميد، حسن بن صالح (جامعة القلم للعلوم الإنسانية والتطبيقية, 2015)
هذا البحث محاولة لتتبع الفرص الإلهية التي أنعم الله بها على عباده وجمع ما يتعلق بها في ثنايا النصوص القرآنية، وإبراز معانيها، ودلالاتها ومتعلقاتها وأنواعها، للاستفادة منها واستثمارها بطريقة صحيحة تثمر نتائج إيجابية في معالجة كثير من نواحي الضعف والقصور الناتجة عن إهمال الفرص أو توظيفها بطريقة خاطئة. باعتبار أن حقيقة الفرصة تتمثل في الحصول على ما ينفع الإنسان في دنياه وآخرته، والتخلص مما يضطر في العاجل والآجل خلافا لنظر كثير من الناس لمفهوم الفرصة.
This research is an attempt to examine the Heavenly Chances Allah has blessed His subjects with, collecting whatever related to them in the Quranic texts and highlighting their meanings, interpretations and types. This is so for getting the benefits from, and exploiting them in the right perspective for treating many human weaknesses, which result from not exploiting them properly. The reality of Chance is getting its benefit in what is good for human, and getting rid of whatever evil that may cause bad consequences on the part of human sooner or later, contra what many people think of the concept of Chance.
Keywords: علوم القرآن -- الفرصة -- الفرصة الدنيوية -- الفرص الدينية